A COMBINATION OF DIABETES MELLITUS AND ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES SOLVING THE PROBLEMS OF DIAGNOSIS AND TREATMENT - Okhunov Alisher Orpovich.; Khamdamov Sherali Abdikhamidovich. (Scholar Express Journals, 2023)
Increasing the effectiveness of treatment of lung abscesses is an urgent problem of thoracic surgery in connection with the increase in the contingent of patients with respiratory diseases, an increase in the number of complications and adverse outcomes of purulent-destructive diseases of the lungs and pleura.
Keywords: pleura; increase; diseases; problem